New Class of Organic Hole-Transporting Materials Based on Xanthene Derivatives for Organic Electronic Applications - Martins, Jefferson S.; Bartolomeu, Aloisio A. [UNESP]; Dos Santos, Willian Henrique [UNESP]; Da Silva Filho, Luiz Carlos [UNESP]; De Oliveira, Eliezer Fernando [UNESP]; Lavarda, Francisco Carlos [UNESP]; Cuin, Alexandre; Legnani, Cristiano; Maciel, Indhira O.; Fragneaud, Benjamin; Quirino, Welber G. (American Chemical Society (ACS), 2017)
In this work, we investigate the influence of three novel 14-aril-14H-dibenzo[a,j]xanthene derivatives (XDs) modified with different functional groups as very promising hole-transporting materials for organic optoelectronic devices. Optical, electronic, and structural properties were analyzed by UV-vis absorption spectrum, cyclic voltammetry, and powder X-ray powder diffraction (XRPD). We investigated the influence of these XD as hole-transporting layers (HTL) on the performance of a simple stack bilayer OLED built with commercial aluminum tris(8-hydroxyquinoline) Alq3 acting as an electron-transporting and emissive layer (EML). As a proof-of-principle the XD devices were compared to reference devices fabricated with one of the most common hole-transporting materials, the N,N′-bis(naphthalen-1-yl)-N,N′-bis(phenyl)-2,2′-dimethylbenzidine (α-NPD). The structure of the devices was ITO/HTL (50 nm)/Alq3 (50 nm)/Al (120 nm) without encapsulation. Under the same conditions, the devices using XD as HTL exhibited high performance and significant durability when compared to the reference ones. These results are also supported by a theoretical study using density functional theory (DFT) showing that this set of XD presents a higher hole mobility than α-NPD. Thus, we demonstrated that this class of molecules are very promising when used as hole-transport material in organic electronic devices.